Environmental conservation in riparian zones of two urban stream in the municipality of Três Pontas, south of Minas Gerais (Research, Society and Development, 2021)
Defining urban permanent preservation areas (APPs), as well as knowing the floristic structure of the riparian vegetation and the environmental quality of the streams, are fundamental factors for planning urban expansion. Given this context, this article aims to assess the state of conservation of the urban riparian zone of the Araras and Formigas streams in the municipality of Três Pontas, MG. The methodology consisted in the application of a Rapid Assessment Protocol. In general, most of the analyzed stretches of the riparian zones of the Araras stream were impacted, while most of the analyzed stretches of the Formigas stream were preserved. The results demonstrate the possibility of characterizing a water body through physical and biological variables of the habitat, as well as the ease of application of the method used. The assessment of the environmental integrity of any ecosystem is the initial step for planning and implementing programs for the maintenance, preservation and restoration of environments and, therefore, a complementary tool that can be used by management agencies of natural resources and urban planning.